The Impact of Three Cognitive Training Interventions on Older Adults' Physical Functioning Across 5 Years. (March 2018) - Ross, Lesley A.; Sprague, Briana N.; Phillips, Christine B.; O'Connor, Melissa L.; Dodson, Joan E.
Objective: Physical functioning is closely associated with cognition. The current study assessed the impact of three cognitive training programs on objective measures of physical functioning across 5 years.Method: Older adults randomized to a processing speed ( n = 702), reasoning ( n = 694), or memory ( n = 703) training intervention were compared with those randomized to a no-contact control condition ( n = 698). Intention-to-treat (ITT) and treatment-received/dosage (time-varying number of training sessions) analyses were conducted.Results: There were no transfer effects in the ITT analyses. Treatment-received models demonstrated that training sessions (i.e., higher dosage) across all intervention arms transferred to better maintained Digit Symbol Copy and Turn 360 performance relative to the control group. More reasoning training transferred to better grip strength.Discussion: This is the first study to demonstrate differential longitudinal cognitive training transfer effects to three performance-based physical functioning measures. Future research should investigate mechanisms of far-transfer effects.